A randomized controlled trial to compare functional, combined rigid and functional and rigid fixation in double mandibular fractures - Sandeep Pandey, MDS; Poonam Yadav, MDS; Ajoy Roychoudhury, MDS, FDSRCPS (Glasgow); Ongkila Bhutia, MDS; Devalina Goswami, MD (Elsevier, 2022)
Purpose: The purpose of the study was to evaluate whether the rigid fixation at one site and functional fixation at other site is enough in double mandibular fractures (DMF). The specific aim of the study was assessment of masticatory function on the basis of bite force and other clinical parameters. Methods: A prospective, randomized controlled trial was conducted on patients having DMF. The patients were randomized into 3 groups. Group-1, managed with 2-miniplates at anterior and 1-miniplate at posterior site, group-2 patients managed with one 2.4 mm reconstruction plate at anterior and 1-miniplate at posterior site and in group-3, both fractures were managed with 1-reconstruction plate. Primary outcome variable was bite force. Secondary outcome variables were type of fracture, pain, swelling, mobility between fracture segments, occlusal discrepancy, paresthesia, implant exposure/fracture. Results: The study sample included 60 (20 in each group) patients with mean age of 29.28 ± 12.35 years. Statistically significant difference was seen in bite force from preoperative to follow-up (p = 0.0) in all the groups. Difference in bite force was statistically significant between group 1 and 2 (p = 0.0) and group 1 and 3 (p = 0.0) at follow-up but the difference was statistically insignificant between group 2 and 3. Conclusion: The present study concludes that treatment of DMF with rigid fixation at one site and functional fixation at other fracture site provides enough fixation.